2012
DOI: 10.4049/jimmunol.1101562
|View full text |Cite
|
Sign up to set email alerts
|

Human T Lymphotropic Virus Type 1 Increases T Lymphocyte Migration by Recruiting the Cytoskeleton Organizer CRMP2

Abstract: Recruitment of virus-infected T lymphocytes into the CNS is an essential step in the development of virus-associated neuroinflammatory diseases, notably myelopathy induced by retrovirus human T leukemia virus-1 (HTLV-1). We have recently shown the key role of collapsin response mediator protein 2 (CRMP2), a phosphoprotein involved in cytoskeleton rearrangement, in the control of human lymphocyte migration and in brain targeting in animal models of virus-induced neuroinflammation. Using lymphocytes cloned from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 85 publications
1
37
1
1
Order By: Relevance
“…25 In the context of HTLV-1 infection, the levels of full-length CRMP2 were always higher (compared with the short version) in infected compared with uninfected T cell clones. 37 Importantly, this correlated with the higher migratory rate of infected T cell clones. In addition, these cells displayed a more pronounced adhesion of full-length CRMP2 to the cytoskeletal components, tubulin and actin.…”
Section: Retroviral Infection Modulates Crmp2 Cleavage To Enhance Lymmentioning
confidence: 92%
See 3 more Smart Citations
“…25 In the context of HTLV-1 infection, the levels of full-length CRMP2 were always higher (compared with the short version) in infected compared with uninfected T cell clones. 37 Importantly, this correlated with the higher migratory rate of infected T cell clones. In addition, these cells displayed a more pronounced adhesion of full-length CRMP2 to the cytoskeletal components, tubulin and actin.…”
Section: Retroviral Infection Modulates Crmp2 Cleavage To Enhance Lymmentioning
confidence: 92%
“…Comparative genomic analyses performed on CD69 + cells selected from HD and HTLV-1 infected patients suffering from TSP/HAM indicated that a number of genes involved in signaling pathways, downstream of chemokine receptors and cell migration, were specifically present in patients. 37 Patient cells exhibited a distinct profile, with 22 genes uniquely expressed and 10 others with a $ 3-fold increased expression. Several are involved in G protein and PI3K signaling.…”
Section: Retroviral Infection Activates the Pi3k/akt/gsk3/crmp2 Axis mentioning
confidence: 99%
See 2 more Smart Citations
“…L'engagement de CADM-1 permet le recrutement de TIAM (T lymphoma invasion and metastasis), un facteur d'échange pour la GTPase Rac, l'activation de Rac et la formation de lamellipodes [25]. Gem et la fascine colocalisent avec l'actine [22,23], mais pas avec Tax, alors que CRMP-2 colocalise avec les microtubules et partiellement avec Tax au niveau des contacts cellule-cellule [26]. CRMP-2 permet l'assemblage des microtubules lorsqu'elle est phosphorylée par ROCK-II (Rho-associated, coiled-coil containing protein kinase 2), une kinase activée par la GTPase Rho, ce qui pourrait contrôler la polarisation du MTOC.…”
Section: Une Capacité Accrue Des Cellules Infectées à Migrerunclassified